Retinal pigment epithelium cholesterol efflux mediated by the 18 kDa translocator protein, TSPO, a potential target for treating age-related macular degeneration. (24th August 2017) - Biswas, Lincoln; Zhou, Xinzhi; Dhillon, Baljean; Graham, Annette; Shu, Xinhua
Abstract: Cholesterol accumulation beneath the retinal pigment epithelium (RPE) cells is supposed to contribute the pathogenesis of age-related macular degeneration (AMD). Cholesterol efflux genes ( APOE and ABCA1 ) were identified as risk factors for AMD, although how cholesterol efflux influences accumulation of this lipid in sub-RPE deposits remains elusive. The 18 kDa translocator protein, TSPO, is a cholesterol-binding protein implicated in mitochondrial cholesterol transport. Here, we investigate the function of TSPO in cholesterol efflux from the RPE cells. We demonstrate in RPE cells that TSPO specific ligands promoted cholesterol efflux to acceptor (apo)lipoprotein and human serum, while loss of TSPO resulted in impaired cholesterol efflux. TSPO -/- RPE cells also had significantly increased production of reactive oxygen species (ROS) and upregulated expression of proinflammatory cytokines (IL-1β and TNFα). Cholesterol (oxidized LDL) uptake and accumulation were markedly increased in TSPO -/- RPE cells. Finally, in aged RPE cells, TSPO expression was reduced and cholesterol efflux impaired. These findings provide a new pharmacological concept to treat early AMD patients by stimulating cellular cholesterol removal with TSPO specific ligands or by overexpression of TSPO in RPE cells.